Genetic diversity of 15 STR loci in Yunnan Va ethnic minority and the phylogenetic relationships with 26 other populations - Xiufeng Zhang; Jing Li; Jingtao Wen (Taylor & Francis Group, 2022)
Background The Va (also called "Wa") people are an ethnic minority living mainly in the southwest of Yunnan Province Aim This study was conducted to obtain the genetic information and forensic statistical parameters of 15 autosomal short tandem repeat (STR) loci included in the AmpFlSTR®Identifiler™ kit (Applied Biosystems, Foster City, CA) in the Yunnan Va population, with a view to enriching the genetic databases of the Chinese Va population. Subjects and methods A total of 508 unrelated Chinese Va individuals were genotyped with this 15 STR kit, the genetic polymorphisms and associated forensic parameters were calculated. The genetic relationships between Chinese Va and 26 other Chinese populations were also evaluated. Results All of the STR loci reached the Hardy-Weinberg equilibrium after Bonferroni correction. A total of 159 alleles were observed with allele frequencies ranging from 0.000984 to 0.606299. The combined discrimination power (CDP) and the cumulative probability of excluding (CPE) of the 15 STR loci were 0.999 999 999 999 999 988 126 and 0.999 995 734, respectively. Our results indicated that the geographically adjacent or ethnically close populations showed a higher genetic affinity. Conclusions The results of this study will enrich the forensic databases of the Chinese Va population and could be applied in forensic analysis.